The Effect of Metanolic Extract and Ethyl Acetate Fraction of Kepel Fruits to Lipid Peroxide Concentration in Liver of CCl4-induced Rat - Mitsalina Fildzah Arifah; Sudibyo Martono; Sugeng Riyanto; Claude Mona Airin (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2019)
Accumulation lipid peroxidation can lead to the formation of malondialdehyde to generatefree radicals. Antioxidant will minimize free radical related health problems, such as naturalantioxidant from meat of kepel (Stelechocarpus burahol) (Blume) Hook. F. & Thompson) fruits.Antioxidant activities of methanol extracts and acetate ethyl fractions meat of kepel fruits calculatedprofile of malondialdehyde concentration (ng/mL) in CCl4 induced acute liver toxicity in femaleSprague Dawley rats using ELISA competitively method. All of groups induced CCl4 i.p. at 0 h, exceptuntreated and solvent control group, then vitamin C , methanol extracts and acetate ethyl fractionsp.o. once daily for 72 h. Identification of secondary metabolite was using phytochemical screeningand Thin Layer Chromatography (TLC). Liver weighed and calculated relative organ weight (ROW)of liver, then all of data analyzed using statistic tests, One Way ANOVA and Kruskall Wallis. Thisstudy showed methanol extracts can decrease MDA concentration, ALT and AST were more potent(significantly p<0.05) than acetate ethyl fractions and vitamin C. The TLC analysis identified methanolextracts have same polarity with quercetin (Rf = 0,26) and acetate ethyl fractions showed otherflavonoid class, except rutin and quercetin. ROW of acute liver toxicity in rats increased significantlyin CCl4 and vitamin C groups.